Translation and psychometric evaluation of the Korean version of the fertility awareness and attitudes towards parenthood questionnaire - Hyewon Shin (Korean Academy of Child Health Nursing, 2021)
Purpose This study presents a translation, cultural adaptation, and psychometric evaluation of two instruments of the Fertility Awareness and Attitudes Towards Parenthood (FAAP) questionnaire (Conditions and Life changes) for use in South Korea. Methods This methodological study included 166 university students for psychometric evaluation in the sixth step. The first five steps included forward translation, backward translation, committee review, assessment of content validity, and a pre-test. In the sixth step, psychometric properties, including internal consistency, construct validity, and criterion validity, were evaluated. Exploratory factor analysis and confirmatory factor analysis were conducted to identify the structure of the tool and to assess its validity. Results The Korean version showed acceptable internal consistency. Cronbach's ⍺ was .73 for FAAPC-conditions and .83 for FAAP-Life changes. FAAP-Conditions showed a four-factor structure (social conditions, relationship with partner, external environment, and child-rearing support) and FAAP-Life changes had a two-factor structure (reward and burden). In the confirmatory analysis, CMIN/DF, TLI, IFI, SRMR, CFI, and RMSEA were satisfactory. Conclusion This study provided preliminary evidence of the acceptability, reliability, and validity of the Korean version of the FAAP questionnaire in university students in South Korea. Nonetheless, further evaluation among Korean young adults is warranted to validate this instrument.